Aktivitas Anticendawan Ekstrak Kecombrang Terhadap Colletotrichum acutatum pada Cabai Rawit: Antifungal Activity of Torch Ginger Extract Against Colletotrichum acutatum on Cayenne Pepper - Imaniasita, Vidya; Wiyono, Suryo; Damayanti, Tri Asmira (Jurnal Fitopatologi Indonesia, 2024)
Antifungal Activity of Torch Ginger Extract Against Colletotrichum acutatum on Cayenne Pepper Torch ginger (Etlingera elatior) is a traditional spice plant that has been widely utilize in Indonesia as an antimicrobial in medical. However, the potential of torch ginger as botanical fungicide in phytopathology needs further study. The research aimed to study the antifungal activity of rhizome and leaf extracts of torch ginger using methanol and ethanol solvents against Colletotrichum acutatum. The extracts was tested using in vitro medium poisoning method at five concentration levels with observation parameter including colony diameter, sporulation, and germination of conidium. The in vivo test was conducted on cayenne pepper fruits with observation parameter such as incubation period, disease intensity and treatment efficacy level. The in vitro study showed that among concentration tested, the torch ginger leaf extract in methanol solvent with a concentration of 2.5% as the best concentration which is inhibits C. acutatum growth, sporulation and germination of conidium by effectiveness up to 66.2%, 99.8% and 100%, respectively in compared to other treatments. The in vivo test on cayenne pepper fruits, the methanol leaf extract at concentration 2.5% inhibits the development of C. acutatum growth, while at concentration 4.8% showed able to prolonged incubation period, reduced disease incidence and severity significantly with effectiveness 88.4% and 96%, respectively in compared to control and other treatments. The antifungal activity of methanol leaf extract of torch ginger against C. acutatum due to its highly phenolic compound. This research successfully demonstrated the potential of extract of torch ginger leaf as botanical fungicide to suppress C. acutatum infection, especially on post-harvest cayenne pepper fruits.